Outcome of Supracondylar Fractures of The Femur with Locking Condylar Buttress Plate (Journal of Pakistan Orthopaedic Association, 2014)
Background: The incidence of distal femur fractures is about 4-7% of all femur fractures. The young are mostly affected due to their involvement in road traffic accidents. Earlier attempts of internal fixation were met with great complications mostly due to unavailability of good fixation devices which would allow early range of motion. With the introduction of the locking plates interest has again developed in fixation of these fractures by these new implants as they allow early range of motion.Objective: The objective of the study was to determine the outcome of Supracondylar Fractures of The Femur with Locking Condylar Buttress Plate Materials andMethods: In this prospective study all the patients operated at department of Orthopedics, Bahawal Victoria Hospital for distal femur fracture fixed by locking condylar buttress plate were followed up for six months or till time of radiological union. Time to union, non-union rate and complications were assessed.Results: Time to union was 117 days (range 90-150 days). There were no cases of non-union in this small series of patients. Only one case of surgical site infection was diagnosed which required immediate attention.Conclusion: Our results are encouraging with better outcome in terms of union and less complications. This enables us to continue this study further to project on a larger patient data so that future recommendations can be framed.Keywords: supracondylar fracture femur, distal femur locking buttress plate